Assessment of the Treatment Strategies of Random housing in Ramadi City from the perspective of Sustainable Transport by Using (AHP&GIS) - ., Thaer Shakir Mahmood; ., Arwa Hazim Ibraheem (Iraqi Journal of Civil Engineering, 2022)
The phenomenon of random housing in Ramadi city is one of the important planning challenges facing the city, especially after rapid growth rates of urban and population grow thing in the city, hence the importance of research is to prove that sustainable transport planning has a prominent role in addressing this problem and producing many social economic and environmental problems. This study aims to determine the role and importance of transport and sustainability planning criteria for the proposed strategies to address the informal housing spread in the city neighborhoods and sectors within and outside the boundaries of the master plan of the city.The use of Analytic hierarchy process (AHP), which combines descriptive and quantitative analysis, will depend on the available data for city at the present time ; as well as, on the expertise of specialists and persons concerned in the subject through a questionnaire to reach the most important factors that affecting random housing from the point of sustainable transport on one hand and in addition to prioritizing treatment according to the proposed strategies presented to planners and local authorities in the city.The research encountered a number of difficulties and obstacles, the most important of which is the scarcity of data and information available in the subject, which led to personally analyze data and resort to the use of geographic information systems (GIS) for the purposes of quantitative and geometrical analysis. The main results for the basic criteria affecting the role of sustainable transport on Ramadi city by gradation from top to lowest ,( i.e. environmental criterion, followed by economic, social, and finally schematic). As for secondary standards, the highest value was the share of the standard of treatment of residential destroyed areas, within the environmental criterion, and the lowest value is the calibration of road efficiency within the planning criterion.